English as a Global Language: Its Influence on Technology and Culture: Bahasa Inggris sebagai Bahasa Global: Pengaruhnya terhadap Teknologi dan Budaya - Cyrilla, Nadhia I’zaz; Ningtyas, Nandyta Hardin; Nafia, Nisa Arrofiatun (Proceedings of International Conference on Islamic Civilization and Humanities, 2025)
English has become the dominant global language, playing a crucial role in international communication, business, and education. Its widespread use is largely due to historical factors such as British colonialism and the economic and cultural influence of the United States. In the modern era, English continues to shape technological advancements and cultural interactions worldwide. The language serves as a bridge in scientific research, digital communication, and global media, making it essential for innovation and cultural exchange. Understanding the impact of English on these aspects helps in assessing its significance in global development. This article is to analyze the role of English as a global language and its influence on technological advancements and cultural development. This article discusses the role of english as a global language and its impact on technological and cultural development in the material of history of english language and literature. This study is expected to contribute to a better understanding of the role of English as a global language and its impact on technology and cultural development. By examining its influence, this research aims to highlight both the opportunities and challenges associated with English’s dominance, particularly for non-native speakers navigating global interactions.